2016
DOI: 10.1002/mrm.26359
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative fat and R2* mapping in vivo to measure lipid‐rich necrotic core and intraplaque hemorrhage in carotid atherosclerosis

Abstract: Purpose The aim of this work was to quantify the extent of lipid‐rich necrotic core (LRNC) and intraplaque hemorrhage (IPH) in atherosclerotic plaques. Methods Patients scheduled for carotid endarterectomy underwent four‐point Dixon and T1‐weighted magnetic resonance imaging (MRI) at 3 Tesla. Fat and R2* maps were generated from the Dixon sequence at the acquired spatial resolution of 0.60 × 0.60 × 0.70 mm voxel size. MRI and three‐dimensional (3D) histology volumes of plaques were registered. The registration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Within a single sequence QSM allows for identification of plaque features such as calcification, USPIO uptake, and potentially paramagnetic intraplaque hemorrhage, which was not present in our patient cohort. Furthermore, a previous study has shown the feasibility of using Dixon‐based water‐fat separation to identify the LRNC of the plaque . In our study, 1 of the plaques, where histology was performed contained a large LRNC, whose presence was confirmed using IDEAL water‐fat separation in addition to QSM analysis.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Within a single sequence QSM allows for identification of plaque features such as calcification, USPIO uptake, and potentially paramagnetic intraplaque hemorrhage, which was not present in our patient cohort. Furthermore, a previous study has shown the feasibility of using Dixon‐based water‐fat separation to identify the LRNC of the plaque . In our study, 1 of the plaques, where histology was performed contained a large LRNC, whose presence was confirmed using IDEAL water‐fat separation in addition to QSM analysis.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, the IDEAL water‐fat separation was able to detect a large LRNC in one of the patients, the presence of which was confirmed on the histological analysis of the carotid endarterectomy specimen with the Elastic Van Gieson histochemical stain, where it could be identified by its yellow/pink coloring and the presence of cholesterol crystals. For MRI, we used a similar analysis to Koppal et al to identify the LRNC as the LRNC was identified by a heightened fat fraction when compared with “normal” plaque regions and the sternocleidomastoid muscle (Figure ). In the same plaque, QSM was able to identify both calcification and USPIO uptake, as described previously (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the study by Koppal et al [63], a 4-point Dixon sequence is used with an OP, IP, OP, IP scheme at echo times of n ⇤ 3.6 [ms]. The use of an additional echo enables the estimation of T ⇤ 2 relaxation (a measure of phasedispersion) times for each voxel.…”
Section: Time After Rf Pulsementioning
confidence: 99%
“…Paper IV built upon the work of Koppal et al [63], where they used a fourpoint Dixon sequence to quantify FF and R ⇤ 2 signal in atherosclerotic plaques of the carotid artery and validated these signals against histological findings. This work was limited in scope by the need for manual segmentation of the plaque boundaries.…”
Section: Quantifying Vessel Wall Compositionmentioning
confidence: 99%